A corpus-based collocational analysis of noun premodification types in academic writing - Ang, Leng Hong; Tan, Kim Hua; He, Mengyu (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study employs a corpus-based method in analysing the noun and noun premodification in journal articles relevant to the field of International Business Management. Following the frequency-based tradition, the noun and noun premodification are identified and extracted by using the node-and-collocate approach. The corpus is divided into five sub-corpora for the purpose of analysing the noun collocations and noun premodification types in each section and between different sections in the journal articles, namely, Introduction, Literature Review, Methods, Results and Discussion sections. The findings show that general adjective is the most common noun premodifier, followed by noun premodifier in both the Introduction and Literature Review sections, whereas general adjective and noun premodifier are both commonly used as premodifiers for nouns in Methods and Results sections. Besides, the general adjective is the most dominant premodifier in Discussion section. The findings also indicate that ed-participial and ing-participial premodifiers are not commonly used in the relevant journal articles. With regard to the use of noun premodification types between different sections in journal articles, general adjective+noun collocation is more pervasive in Introduction, Literature Review and Discussion sections. On the other hand, noun+noun collocation is more commonly found in Methods and Results sections. Following Hoey’s Lexical Priming, the results show that priming occurs at grammatical level within the discourse. The noun collocations identified are compiled for the possible use in the English for Academic Purposes Course.